Tortrix viridana L. (Lepidoptero Tortricidae) una plaga de las encinas de problematico control - Soria, S.=700 1 Notario, A.
(En, Es)
ilus., 70 ref.
Keywords: TORTRIX VIRIDANA; QUERCUS; LUCHA INTEGRADA; ESPAÑA